Algebraic Strategies for Predictions in Elementary Mathematics Education - Nikolovska, Gordana; Stojkovska, Irena (Union of Mathematicians of Macedonia, 2016)
Algebraic thinking and reasoning is an important process in mathematics education, during which mathematical ideas are generalized from a specific set of instances, and the conclusion of the generalization is represented in different ways depending on the students' age. Algebraic strategies can be also used for practicing the students' prediction abilities, which can be beneficial while learning new concepts, and making connections to concepts that have been already learned. We have chosen patterns and number sequences as an initial step for exercising the prediction abilities in order to develop algebraic, functional and mathematical thinking among students in elementary education.
Keywords: Algebraic thinking, algebraic reasoning , algebraic strategies